2005
DOI: 10.1080/09273970500455436
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Convergence Insufficiency and ADHD

Abstract: We report an apparent three-fold greater incidence of ADHD among patients with CI when compared with the incidence of ADHD in the general US population (1.8-3.3%). We also note a seeming three-fold greater incidence of CI in the ADHD population. This may simply represent an association and not be a causative relationship. Until further studies are performed, however, patients diagnosed with ADHD should be evaluated to identify the small subset that may have CI -- a condition that responds well to treatment at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
3
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 14 publications
8
82
3
6
Order By: Relevance
“…The disorder is much less common in children younger than 10 years. The incidence of ADHD was reported in 1 study to be increased in children with convergence insufficiency, 145 but additional analysis has revealed that the reported incidence was actually average when compared with large studies in which the prevalence of ADHD was evaluated. 17,18 Convergence amplitudes have not been correlated with reading comprehension.…”
Section: Accommodationmentioning
confidence: 97%
“…The disorder is much less common in children younger than 10 years. The incidence of ADHD was reported in 1 study to be increased in children with convergence insufficiency, 145 but additional analysis has revealed that the reported incidence was actually average when compared with large studies in which the prevalence of ADHD was evaluated. 17,18 Convergence amplitudes have not been correlated with reading comprehension.…”
Section: Accommodationmentioning
confidence: 97%
“…В других случаях, выявляя пато-логию рефракции, офтальмолог выписывает сред-ство коррекции, однако не углубляется в изучение бинокулярного зрения, и проблема снова остается нерешенной [10].…”
Section: погляд на пробемуunclassified
“…Симптомы НК, соз-дающие трудности с концентрацией внимания, могут совпадать с симптомами СДВГ. CITT показа-ло, что у 45% детей с НК снижается способность к концентрации внимания [10].…”
Section: отдаление ближайшей точки конвергенции (бтк)unclassified
See 2 more Smart Citations